2020
DOI: 10.3390/su122410252
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Volumes as a Modal Split Parameter

Abstract: Traffic volume depends on several indicators. The most important are the degree of motorization, mobility, and especially the travel time and travel cost factor. The article presents an analysis of the possibility of using mobility surveys and traffic counts to achieve a balance between supply and demand. The frequency of congested traffic and over-capacity volumes are determined. By analyzing the trip information captured in the mobility surveys, we detected the strata causing the highest demand—economically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
2
8
2
Order By: Relevance
“…This is a confirmation that modal split can differ among cities because of the peculiarity of determinant factors (such as religion in Enugu city). The outcome of this study is competitive in accuracy with the discrete choice models (Al-Salh & Esztergas-Kiss, 2021; Drliciak et al, 2020;Novacˇko et al, 2020;Obaid & Hamad, 2020;Rasaizadi & Askari, 2020). This supports the discussions in the theory and methodology sections of this study, which indicate that the discriminant analysis (a probabilistic model) is a robust model for estimating the modal split of intra urban trips.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This is a confirmation that modal split can differ among cities because of the peculiarity of determinant factors (such as religion in Enugu city). The outcome of this study is competitive in accuracy with the discrete choice models (Al-Salh & Esztergas-Kiss, 2021; Drliciak et al, 2020;Novacˇko et al, 2020;Obaid & Hamad, 2020;Rasaizadi & Askari, 2020). This supports the discussions in the theory and methodology sections of this study, which indicate that the discriminant analysis (a probabilistic model) is a robust model for estimating the modal split of intra urban trips.…”
Section: Discussionmentioning
confidence: 69%
“…Most of the plethora of studies on the modal split of intra urban trips found in the literature focused on Europe, America and Southeast Asia with little emphasis on Africa. These studies (such as Bucsky, 2020; Chen et al, 2015; Drliciak et al, 2020; Guerra & Li, 2021; Novačko et al, 2020; Li et al, 2021; Mendiola & Gonzalez, 2021; Shukla, 2019) explains the modal split of intra urban trips and its causal factors. The outcome of most of these studies show private transport as a popular mode used for intra urban trips in their respective cities.…”
Section: Introductionmentioning
confidence: 99%
“…Road traffic is characterized by basic parameters such as traffic volume (the proportion of trucks), density, and speed of traffic flow (Cingel et al, 2019;Drliciak et al, 2020). In the tunnel tube where the PM measurements were performed, the traffic volume was recorded as 2,280 veh/24 h on average, and in the other tunnel tube, it was 2,428 veh/24 h on average.…”
Section: Particulate Matter In the Tunnel Environmentmentioning
confidence: 99%
“…These outputs can be used to analyse the existing communication network, evaluate the alternative solutions, evaluate the impacts and influences on the surrounding transport network or the environment, analyse traffic service, etc. For example, [30] deals with the issue of optimal distribution of passengers between individual car transport and public transport using macrosimulation models created in the PTV VISUM program and focuses on the area of Kysuce and the city Žilina in Slovakia. The same authors also deal with the analysis of transport in the town of Martin [31].…”
Section: About Traffic Modelling In Generalmentioning
confidence: 99%